2021
DOI: 10.1101/2021.03.22.21254032
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D-related polymorphisms and vitamin D levels as risk biomarkers of COVID-19 infection severity

Abstract: Background: Vitamin D is a fundamental regulator of host defences by activating genes related to innate and adaptive immunity. Previous research shows a correlation between the levels of vitamin D in patients infected with SARS-CoV-2 and the degree of disease severity. This work investigates the impact of the genetic background related to vitamin D pathways on COVID-19 severity. For the first time, the Portuguese population was characterized regarding the prevalence of high impact variants in genes associated … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…A study which aimed to assess the association between variants in the GC gene that encodes vitamin D binding/transport protein (DBP), and the prevalence and mortality rates of COVID-19, pointed out to rs7041 variant (42). Another recent study (not peer-reviewed yet) performed in Portuguese population of COVID-19 patients found an association of GC rs2282679 variant with COVID-19 disease severity (43). Our study indicated an association between DHCR7/NADSYN1 rs12785878 and CYP2R1 rs10741657 variants and the severity of COVID-19, but the variants GC rs2282679 and VDR rs2228570 were not linked to a higher risk of severe COVID-19 in adults.…”
Section: Discussionmentioning
confidence: 99%
“…A study which aimed to assess the association between variants in the GC gene that encodes vitamin D binding/transport protein (DBP), and the prevalence and mortality rates of COVID-19, pointed out to rs7041 variant (42). Another recent study (not peer-reviewed yet) performed in Portuguese population of COVID-19 patients found an association of GC rs2282679 variant with COVID-19 disease severity (43). Our study indicated an association between DHCR7/NADSYN1 rs12785878 and CYP2R1 rs10741657 variants and the severity of COVID-19, but the variants GC rs2282679 and VDR rs2228570 were not linked to a higher risk of severe COVID-19 in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Investigating the influence of the DBP phenotypes in patients with a Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) infection, we demonstrated that DBP1 carriers might be less susceptible to infection and mortality due to COVID-19 (Speeckaert et al, 2021). Besides, in a recent paper, a positive correlation was observed between the Metabolism score (= DBP rs2282679 + CYP24A1 rs17216707) and COVID-19 disease severity, in which a deeper analysis showed that the rs2282679 polymorphism could explain most of this interesting correlation (Freitas et al, 2021). Besides the transport of vitamin D and its metabolites, DBP could exert several other key roles in COVID-19, being involved in the extracellular actin scavenger system or acting as a neutrophil chemotactic factor and a macrophage activator (Delanghe et al, 2015).…”
mentioning
confidence: 71%
“…To support this statement, we have investigated in a previous report ( 6 ) the influence of the DBP phenotypes in patients with a severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection by comparing the frequency of the DBP1 allele (a mixture of DBP1F and DBP1S) with the prevalence and mortality data of COVID-19 in 55 countries. An association was observed between the DBP1 allele frequency and a lower prevalence and mortality due to a SARS-CoV-2 infection, which could be partly explained by the potential protective effects of vitamin D. In another study ( 7 ) that investigated the impact of patient genetic background related to vitamin D pathways on COVID-19 severity, the SNP rs2282679 could explain most of the positive correlation between the metabolism score (DBP rs2282679 + CYP24A1 rs17216707) and COVID-19 severity (ρ = 0.13, P value = 0.005) ( 7 ). Besides the DBP gene, the CYP2R1 gene (rs10741657), the CYP24A1 gene (rs6013897), and the DHCR7/NADSYN1 region (rs12785878) are also genetic determinants of the 25(OH)D concentration.…”
mentioning
confidence: 90%
“…Besides the DBP gene, the CYP2R1 gene (rs10741657), the CYP24A1 gene (rs6013897), and the DHCR7/NADSYN1 region (rs12785878) are also genetic determinants of the 25(OH)D concentration. However, no association has been found between the vitamin D total score (DHCR7 rs12785878 + CYP2R1 rs10741657 + DBP rs2282679 + CYP24A1 rs17216707 + AMDHD1 rs10745742 + SEC23A rs8018720) and the severity of COVID-19 ( 7 ).…”
mentioning
confidence: 99%